2020
DOI: 10.1177/1054773820984911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Focusing on Maryam’s Flower During the First Stage of the Labor on the Labor Pain, Labor Duration, and Levels of Comfort and Satisfaction

Abstract: This randomized controlled experimental study was conducted with an intervention group ( n = 61) and a control group ( n = 63) consisting of primipara pregnant women. The pregnant women in the intervention group were asked to focus their attention on Maryam’s flower opening its leaf buds and imagine the labor’s progress during the course of their labor. The VAS was administered to each group at specific times (at 4–5 cm, 6–7 cm, 8–9 cm cervical dilatation) to determine their level of labor pain. A statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Midwifery care in childbirth aims to reduce the perceived pain of the pregnant woman and provide physical and emotional comfort for them. 1,2,13 In this study, ice massage applied to the SP6 point at 4 to 5 cm, 6 to 7 cm, and 8 to 9 cm cervical dilatation reduced perceived labor pain. In other studies, the labor pain levels of cold massage groups have been found to be significantly lower than control groups.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Midwifery care in childbirth aims to reduce the perceived pain of the pregnant woman and provide physical and emotional comfort for them. 1,2,13 In this study, ice massage applied to the SP6 point at 4 to 5 cm, 6 to 7 cm, and 8 to 9 cm cervical dilatation reduced perceived labor pain. In other studies, the labor pain levels of cold massage groups have been found to be significantly lower than control groups.…”
Section: Discussionmentioning
confidence: 58%
“…Managing labor pain, increasing comfort, and reducing anxiety are among the basic elements of midwifery care. [1][2][3][4][5][6] Pharmacologic methods that reduce labor pain have various side effects on fetal and maternal health. 3,7 Therefore, nonpharmacologic methods, which usually have no side effects for the fetus and the woman and provide comfort, should be offered among the different options for pain management.…”
Section: Introductionmentioning
confidence: 99%
“…Midwifery care in childbirth aims to reduce perceived pain of the pregnant women and to provide physical and emotional comfort for them. 1,2,13 In the present study, it was determined that ice massage applied to SP6 point at 4-5 cm, 6-7 cm, and 8-9 cm cervical dilatations reduced perceived labor pain. Only one study was encountered in the literature in which the effects of ice massage applied to SP6 point in reducing labor pain were examined.…”
Section: Discussionmentioning
confidence: 61%
“…As no study was encountered in the literature which examined the effect of ice massage applied to SP6 point on childbirth comfort, comparisons were made with studies that investigated the effects of various non-pharmacological methods on comfort in childbirth. 1,2,33,34 Turkmen and Oran (2021) reported that warm application to sacral region in childbirth had positive effects on the total comfort and relaxation levels determined at 8-9 cm cervical dilatation. 2 Akin et al ( 2022) reported in their study that labor dance at 8 cm cervical dilatation had positive effects on the total comfort and relaxation levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation